NLRP3 and mTOR Reciprocally Regulate Macrophage Phagolysosome Formation and Acidification Against Vibrio vulnificus Infection - Huang, Xian-Hui; Ma, Yao; Zheng, Meng-Meng; Chen, Na; Hu, Mei-Na; Wu, Liu-Ying; Zheng, Yi; Lou, Yong-Liang; Xie, Dan-Li (Frontiers in Cell and Developmental Biology, 2020)
The marine bacterium Vibrio vulnificus (V. vulnificus) causes potentially fatal bloodstream infections, typically in patients with chronic liver diseases. The inflammatory response and anti-bacterial function of phagocytes are crucial for limiting bacterial infection in the human hosts. How V. vulnificus affects macrophages after phagocytosis is unclear. In this report, we found the bactericidal activity of macrophages to internalized V. vulnificus was dependent on mTOR and NLRP3 interaction. Additionally, the NLRP3 expression was also dependent on mTORC1 activity. Inhibited mTORC1 or absence of NLRP3 in macrophages impaired V. vulnificus-induced phagosome acidification and phagolysosome formation, leading to a reduction of intracellular bacterial clearance. mTORC1 signaling overactivation could increase NLRP3 expression and restore insufficient phagosome acidification. Together, these findings indicate that intracellular bactericidal activity of macrophages responding to V. vulnificus infection are tightly controlled by the crosstalk of NLRP3 and mTOR, and provide critical insight into the host bactericidal activity basis of clearance V. vulnificus through lyso/phagosome.